STUDI FENOMENOLOGI: MAKNA LARANGAN-LARANGAN ADAT ADE' ASSAMATURUSENG DALAM PEMANFAATAN DANAU TEMPE DI KABUPATEN WAJO - Muhammad Ansarullah S. Tabbu; M Fikri Amrullah (JAMBURA GEO EDUCATION JOURNAL, 2022)
The tradition and local wisdom of the Bugis fishermen's community in the management of Lake Tempe is a visible social reality (phenomenon) in the form of a set of customs called Ade' Assamaturuseng. The purpose of this study is to reveal the meaning (noumena) of the actions of Bugis fishermen in the use of Lake Tempe as a visible reality (phenomena) based on customary local prohibitions called Ade' Assamaturuseng (customs that are obeyed together). The research method used is a qualitative research method with a phenomenological approach to the perspective of Alfred Schurtz. Data collection techniques include in-depth interviews, participant observation, and documentation studies. The results of the research show that the prohibitions in the Ade' Assamaturuseng custom are the background contexts (because of the motives) for the actions or behavior of fishermen in utilizing Lake Tempe. These actions or behaviors have objective motives (in order motives) so that they contain meaning as in the statements of the research subjects about the custom. In Schurtz's phenomenological perspective, the meaning of fishermen's actions based on the customary prohibitions of Ade' Assamaturuseng, among others; (1) Means as a conservation effort; (2) Means social justice; (3) Meaning as the practice of belief and religion. From the findings, it can be understood that the traditions and local wisdom of Bugis fishermen in the management of Lake Tempe contain the dimensions of values in environmental conservation, togetherness (justice), and culture comprehensively. It can be seen that the behavior of the Bugis fishing community is very respectful of the natural environment as part of their lives and realizes the use of Lake Tempe sustainably and equitably.